2015
DOI: 10.1111/aji.12426
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection and Evaluation of Four Subsets of CD4+ T Lymphocyte in Lesions and Peripheral Blood in Endometriosis

Abstract: The CD4+ T-lymphocyte profile in lesions and peripheral blood is altered in women with endometriosis. These findings may help better understanding of T-lymphocyte involvement in the pathophysiology of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 47 publications
5
58
0
Order By: Relevance
“…Treg is another subset of helper T cells and they are known to maintain immunological tolerance . Many studies have shown that Treg are increased in the peritoneal cavity of endometriosis patients; however, two studies did not find a significant difference . In a mouse study, the inhibition of Treg induction (differentiation) reduced the number and weight of endometriotic lesions .…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Treg is another subset of helper T cells and they are known to maintain immunological tolerance . Many studies have shown that Treg are increased in the peritoneal cavity of endometriosis patients; however, two studies did not find a significant difference . In a mouse study, the inhibition of Treg induction (differentiation) reduced the number and weight of endometriotic lesions .…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, Th2 cytokines, such as IL‐4, IL‐10, and TSLP, have been shown to contribute to disease progression. Studies of peripheral blood, however, have revealed a higher Th1/Th2 cytokine ratio and Th1 cell frequency in endometriosis patients compared with controls. The discrepancy between the local and systemic Th1/Th2 balance remains unresolved.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations